Bridging the diagnostic gap! Behavioral tests for acute vestibular disorders - Abdelkader Aljasem; Samer Mohsen (The Egyptian Journal of Otolaryngology)
Abstract Background Acute vestibular disorders are common, multifaceted conditions affecting individuals of all ages. Diagnostic challenges often arise due to inaccurate questioning and limited clinical findings, leading to delayed management and increased morbidity and mortality. Methods This study evaluated the diagnostic utility of five behavioral vestibular tests (gaze, head-shaking nystagmus, Romberg test, Dix-Hallpike maneuver, and dynamic visual acuity) in patients with acute vestibular disorders. A total of 96 patients underwent a specialized questionnaire, the tests, and subsequent follow-up for final diagnosis. Results Statistical analysis revealed that the combination of these tests, in conjunction with questionnaire data and follow-up, significantly improved the identification of high-risk central vestibular cases. Head-shaking nystagmus emerged as the most valuable test in this regard. While the gaze, Romberg test, and Dix-Hallpike maneuver demonstrated some diagnostic potential, their sensitivity could be enhanced by incorporating additional tests. Dynamic visual acuity, however, did not contribute significantly to the preliminary diagnosis. Conclusion Behavioral vestibular tests are valuable tools for the early diagnosis of acute vestibular disorders, especially in cases requiring rapid assessment and management. Future research with larger sample sizes is needed to further refine the optimal diagnostic protocol and explore the potential of additional tests.